Occurrence of plasmidic AmpC β-lactamase in a Salmonella Typhimurium isolate of equine origin: First report of CMY-2 in animals in Argentina - Dominguez, Johana Elizabeth (2015)
The increase in transferable resistance to third-generation cephalosporins in zoonotic Salmonella constitutes a serious public health threat. Resistance to third-generation cephalosporins is mainly due to acquisition of genes encoding extended-spectrum β-lactamases or AmpC β-lactamases. These genes are mainly plasmid-encoded and are transferable into various serovars of Salmonella and other enteric bacteria. CMY-type enzymes are the most common plasmid-mediated AmpC β-lactamase among Enterobacteriaceae [1]. A variety of plasmids have been shown to carry the blaCMY-2 gene and some of them may be associated with particular Salmonella serotypes from environmental sources. Although CMY-2-producing Salmonella have been found in humans and animals in many countries and regions, isolates from animals has not been previously reported in Argentina.